Medicine: Yesterday, Today and Tomorrow - Fradin D. B.; Katz R. S.; Michels V. V. (Chicago Childrens Press, 1989)
Surveys the history and current status of the field of medicine and makes future projections about such developments as genetic engineering and the conquest of disease.
Keywords: 61